A Single Case Study of Ayurvedic Management of Mandal Kushtha w.s.r. to Psoriasis - Bhaskar, Ayushi; Sharma, Indumati (International Research Journal of Ayurveda & Yoga, 2020)
Mandala kushta is a skin disorder with a preponderance of Sleshma and is classified as Mahakushta. Red spots, elevated patches, itching and burning sensations, and other symptoms of illness are typical. Kledakar Ahar, Dosha vaishamyan, Srotavarodham, Vegadharana, Krimi, Manovikaras, and other factors can contribute to Mandala kushta pathogenesis. Because the condition involves vitiation of the Tri-dosha, Rakta, Mamsa, and Twak, The use of herbs and traditional Ayurvedic formulations helps to cure Mandal kushta by calming vitiated Doshas, improving the quality of Rasa and Rakta, maintaining hormonal balances, and empowering digestive or metabolic activity In light of this, the current essay discussed the ayurvedic perspective on Mandala kushta, with a special focus on saman Chikitsa, in terms of disease management.